Answer:
(- 6, 9 )
Explanation:
Given the 2 equations
9x + 6y = 0 → (1)
- 9x + y = 63 → (2)
To solve by substitution
Rearrange (2) expressing y in terms of x by adding 9x to both sides
y = 9x + 63 → (3)
Substitute y = 9x + 63 into (1)
9x + 6(9x + 63) = 0 ← distribute and simplify left side
9x + 54x + 378 = 0
63x + 378 = 0 ( subtract 378 from both sides )
63x = - 378 ( divide both sides by 63 )
x = - 6
Substitute x = - 6 into (3) for corresponding value of y
y = 9(- 6) + 63 = - 54 + 63 = 9
Solution is (- 6, 9 )